Francisco Franco - Garza, Hedda (New York : Chelsea House, 1987)
Traces the life of the Spanish leader who controlled Spain from 1939 until his death in 1975.
Includes index.
Bibliography: p. 108.
Booklist.
School Library Journal.
Wilson's Junior High School.
7.0
Keywords: Franco, Francisco, -- 1892-1975 -- Juvenile literature; Franco, Francisco, -- 1892-1975.; Franco, Francisco, -- 1892-1975.; Heads of state -- Spain -- Biography -- Juvenile literature; Heads of state; Heads of state -- Spain -- Biography; Spain -- History -- 20th century -- Juvenile literature; Spain -- History -- 20th century; Spain -- History